Genetic predisposition influences plasma lipids of participants on habitual diet, but not the response to reductions in dietary intake of saturated fatty acids. - Walker, C; Loos, R; Olson, A; Frost, G; Griffin, B; Lovegrove, J; Sanders, T; Jebb, SA (2011)
OBJECTIVE: SNPs identified from genome-wide association studies associate with lipid risk markers of cardiovascular disease. This study investigated whether these SNPs altered the plasma lipid response to diet in the 'RISCK' study cohort. METHODS: Participants (n=490) from a dietary intervention to lower saturated fat by replacement with carbohydrate or monounsaturated fat, were genotyped for 39 lipid-associated SNPs. The association of each individual SNP, and of the SNPs combined (using genetic predisposition scores), with plasma lipid concentrations was assessed at baseline, and on change in response to 24 weeks on diets. RESULTS: The associations between SNPs and lipid concentrations were directionally consistent with previous findings. The genetic predisposition scores were associated with higher baseline concentrations of plasma total (P=0.02) and LDL (P=0.002) cholesterol, triglycerides (P=0.001) and apolipoprotein B (P=0.004), and with lower baseline concentrations of HDL cholesterol (P<0.001) and apolipoprotein A-I (P<0.001). None of the SNPs showed significant association with the reduction of plasma lipids in response to the dietary interventions and there was no evidence of diet-gene interactions. CONCLUSION: Results from this exploratory study have shown that increased genetic predisposition was associated with an unfavourable plasma lipid profile at baseline, but did not influence the improvement in lipid profiles by the low-saturated-fat diets.